Beyond Income in Transition Economies: Evaluating Multidimensional Poverty, Informal Employment, and Market Restructuring in Uzbekistan - Abdumalik Oripov; Islomjon Bakhromov (Apollo: Journal of Tourism and Business, 2026)
Conventional income-based poverty metrics have consistently demonstrated inadequate diagnostic effectiveness in transition countries, as post-Soviet restructuring has transformed welfare conditions in ways that monetary consumption measures cannot adequately capture. This paper examines Uzbekistan's methodological and policy move from measuring monetary poverty to a multidimensional, capability-based framework, situating this transition within the wider backdrop of economic change and social policy reform in Central Asia. The analysis employs the Alkire-Foster methodology to implement a national Multidimensional Poverty Index (MPI) that includes the fundamental dimensions of education, health, and living standards, while systematically incorporating labor market dynamics and informal employment into the capability assessment. The study identifies the key non-income factors influencing welfare, emphasizing international migration and remittances as vital economic mechanisms: migration reduces perceived poverty and reallocates household spending towards health and non-food consumption, alleviating capability deprivation. Moreover, community-focused social support from mahalla organizations and strategic state investments in human capital are vital institutional mechanisms for skill development; however, regional disparities and distributional inefficiencies hinder their fair accessibility in the labor market. The utilization of sub-national instruments, specifically the Child Well-Being Index and the Poverty Resilience Index, illustrates the practical importance of multidimensional metrics for focused policy assessment. By incorporating these dimensions into a mixed-methods framework that amalgamates MPI data, qualitative institutional evidence, and household survey analysis, the paper demonstrates that an evidence-based, capability-oriented approach—alongside labor market formalization—serves as a markedly more effective tool for poverty alleviation in Uzbekistan compared to traditional income-centric strategies.